CO35 | Bleeding phenotype characterization in patients with congenital bleeding disorders: a multigenic approach using next generation sequencing to identify coagulation-modulating variants (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Congenital bleeding disorders, including hemophilia A (HA), hemophilia B (HB), and rare bleeding disorders (RBDs), often display variable clinical phenotypes not fully explained by a single pathogenic variant. Additional genetic variants modulating the coagulation cascade may influence bleeding severity. This study aimed to investigate such variants using a multigenic sequencing approach. Methods: Eighteen patients with a previously confirmed diagnosis of congenital bleeding disorder were selected for analysis. The cohort included individuals with HA, HB, FV deficiency, FXI deficiency, and plasminogen deficiency, all followed at the Hemophilia Center of Padua University Hospital. Genetic analysis was performed using a custom Next-Generation Sequencing (NGS) panel (xGen™ Hyb Panel, Integrated DNA Technologies) targeting 33 coagulation-related genes: A2M, CPB2, F2, F3, F5, F7, F8, F9, F10, F11, F12, F13A1, F13B, FGA, FGB, FGG, KLKB1, KNG1, PLAT, PLG, PROC, PROCR, PROS1, PROZ, SERPINA5, SERPINA10, SERPINC1, SERPIND1, SERPINE1, SERPINF2, TFPI, THBD, VWF. Sequencing was performed on the Illumina NextSeq550 platform. Variants with a minor allele frequency <0.1% were classified according to ACMG criteria.